(untitled) (Archives of Criminology, 2023)
Background: The aim of this paper is to explain change and continuity in the Polish drug policy over the past 25 years using the policy constellations framework (Stevens, Zampini 2018). Method: The policy constellations framework is applied to explain Poland’s adoption of solutions based on prohibition in the year 2000, and later from 2008 to 2016, in the context of novel psychoactive substances. The data comes from in-depth interviews with stakeholders (N = 18), including NGO workers, former ministers, government officials, journalists, a former police superintendent and a criminologist. Conclusion: The Polish drug policy is not a natural outcome of events, but it rather reflects moral preferences and material interests (e.g., the desire to reproduce political capital) of the dominant groups involved in shaping the drug policy.